Lymphoid-specific antigen: distribution and behaviour - Potworowski, E. F. (1968)
The distribution of a lymphoid-specific antigen has been studied by immunofluorescence in the thymus and other lymphoid organs of the rat and in the thymuses of other vertebrate species. It was demonstrable in all rat lymphocytes except those of the bone marrow. The thymic lymphocytes of all warm-blooded vertebrates also reacted with the lymphoid-specific serum. Plasma cells in antigenically stimulated lymph nodes did not seem to possess the antigen but similar cells appearing in lymph nodes of rats which had been irradiated and injected with marrow cells of the same strain showed a strong reaction with the antiserum. The antigen is depleted in human and murine leukaemic lymphocytes. X-irradiation did not appear to affect the antigen significantly in cells surviving the treatment.